Perception of Health-Impacts of Environmental Noise in an Ambient Noise Context in Owerri -Urban , Imo State, Nigeria - Ubuoh Emmanuel Attah; S.M.O. Akhionbare; O.A. Onifade; Ogbuji S. I. (International Journal of Advances in Applied Sciences, 2012)
This paper reports the results of the investigation of health impacts of environmental noise context in Owerri-urban, due to incessant complains of urban dwellers of noise pollution and their effects on the health. This was measured by the use of 210 questionnaires on urban dwellers along the major routes, in which 30 questionnaires  were randomly  administered  between sampled routes designated  NP1- NP7. The observed results indicate that , automobile  has 32.3%, church 3.3%, construction work 19.5%, market 5.7%, industrial activities 9.0%, hawking 10%, and school 6.6%, with  automobile recording the highest response as  the main source of environmental noise pollution and church having the least response. For the perceived health problems caused by environmental noise, the results further shown that  Cardiovascular and Physiological effects constituted 20.5%, Hearing Impairment 25.2%, Sleeplessness 21.9%, mental health 11.4%, annoyance 6.6% and human performance 14.2%, with hearing impairment  ranking the highest  and the lowest being annoyance. Environmental noise was  at the peak between the hours of 8- 11 am constituting 49.1%. The hours between 3-7 pm constitutes 39.5%, while <10pm has 11.4% indicating noise pollution is less in the evening time of the day where people are indoor for rest. These then calls for best management practice like enforcement of pollution law, maintenance of vehicles and creation of awareness on health implications of environmental noise.